Pendidikan Islam Berbasis Moderasi Beragama pada Anak Usia Dini - Hulu, Mirwansyah; Sahyan, Sahyan (AUD Cendekia: Journal of Islamic Early Childhood Education, 2025)
This study aims to describe the implementation of Islamic education based on religious moderation for early childhood at RA Syafiiyah, identify the values of moderation instilled through learning activities, and analyze the role of teachers and the school environment in fostering a moderate, tolerant, and respectful attitude among children. The study employs a qualitative approach with a phenomenological design, involving five teachers and ten children as informants, and utilizes curriculum documents, activity records, and participatory observations as secondary data sources. The findings indicate that the implementation of Islamic education based on moderation is carried out through the integration of the curriculum, daily habituation activities, structured social interactions, and teacher role modeling. Religious moderation values such as tolerance, inclusivity, justice, patience, empathy, and respect for differences are internalized through direct learning experiences, group activities, and daily routines. Teachers and the school environment function as models, facilitators, and value enhancers through collaboration with parents and the cultivation of an inclusive school culture. This study provides new insights by emphasizing the holistic implementation of religious moderation in early childhood and offers practical guidance for other PAUD/RA institutions in fostering moderate attitudes from the earliest stages of education.